Application of protein extracted from wheat germ as natural coagulant for palm oil mill effluent using oscillatory flow reactor - Daud, Nor Shazwani (2015)
This research has been concerned with coagulation process using a natural coagulant known as wheat germ to treat the palm oil mill effluent (POME). The performance of wheat germ in the coagulation process was assessed using a jar test through the study of several effects that affects the coagulation process in the jar test. The effects being studied were extractions of wheat germ using different solvent, wheat germ dosage, pH of POME, mixing speed, mixing time and sedimentation time. The wheat germ was extracted using different solvents; distilled water, tap water and salt solution (using sodium chloride (NaCl) with different molar concentration 0.25 M, 0.5 M and 1M). It was found that the wheat germ extracted with 1 molar concentration of sodium chloride (WG-1M) obtained the highest removal of investigated parameters i.e. turbidity, total suspended solid (TSS), chemical oxygen demand (COD) and colour. Following to this,WG-1M was applied throughout the whole experimentation process. The optimum condition in the jar test obtained at 12 000 mg/L of WG-1M dosage, at original pH of POME i.e. 5 with rapid mixing of 120 rpm for 1 minute and slow mixing 35 rpm for 20 minutes at mixing time of 20 minutes in the jar test and 1 hour sedimentation time. The removals were found to be 97.7%, 93.5%, 55% and 65.2% for the turbidity, TSS,COD and colour, respectively. The coagulation process using WG-1M was then conducted in the oscillatory flow mixing reactor (OFR). The effects being studied in the OFR were the effects of baffles spacing, effect of frequency and amplitude, effect of mixing time in the OFR, sedimentation time and WG-1M dosage. The effectiveness of coagulation process in the OFR was assessed through the comparison of the result obtained in the OFR with those obtained in the jar test. The highest removal of turbidity, TSS COD and colour were obtained at frequency of 1 Hz and amplitude of 12 mm which corresponds to Re0 of 6786. This highest removal also achieved when all baffles applied in the OFR at 10 minutes mixing time and 4 hour sedimentation time with the same optimum dosage as obtained in the jar test i.e. 12 000 mg/L. The highest removals of turbidity, TSS COD and colour were 99.5%, 96%, 81.3% and 68.9% respectively. This is higher as compared to coagulation process in the jar test. The result shows that the coagulation process which traditionally done in the jar test can besuccessfully applied in the OFR. It was found that the removal of investigated parameter was further improved and enhanced. The study showed that the wheat germ could be regarded as a new potential natural coagulant for the treatment of POME.